The Potential Antioxidant Of Nanoparticle Of Limus (Mangifera foetida Lour) Seed Kernel Extract - Nurviana, Vera (Jurnal Farmasi Udayana; Spesial Issue, Desember 2020DO - 10.24843/JFU.2020.v09.i03.p02, 2020)
The antioxidants are compounds that have the ability to inhibit free radical activity that causes degenerative diseases. One source of natural ingredients known to have antioxidant activity is limus ( Mangifera foetida Lour.), One of mango species from the Anacardiaceae tribe which is a local Indonesian fruit. Limus seed kernel extract (EBL) has been shown to have antioxidant activity. Antioxidant activity can be increased by making nanoparticle preparations. This study aims to increase the antioxidant activity of limus seeds by modifying the extract into nanoparticle preparations. The preparation of nanoparticles was carried out by the ionic gelation method and to ensure the formation of extract nanoparticles, characterization was carried out including particle size, polydispersion index and zeta potential value. The increase in antioxidant activity of limus seed extract (NEBL) nanoparticles was carried out by comparing the IC 50 value with the IC 50 EBL value, and to see its potential by comparing it with vitamins. The method of measuring antioxidant activity used is the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. IC 50 data were analyzed using the One Way Annova test and post-hoc LSD test with a confidence level of 95%. Based on the research results, it was obtained that limus seed extract nanoparticles were prepared which had characteristics including; The particle size was 2.91 nm, the polydispersion index value was 0.456 and the zeta potential value was +56 mV and the IC 50 value was 1.166 ± 0.021 µg/mL. The IC 50 value of the EBL is 9.127 ± 0.022 µg/mL and Vitamin C is 3.933 ± 0.013. µg/mL Modification of EBL into NEBL preparations can increase antioxidant activity and has excellent potential as a natural antioxidant because it has stronger antioxidant activity than vitamin C (p <0.05). Keywords: Antioxidant, Limus, Mangifera foetida Lour, Nonoparticle